Livelihood Strategies of Male- And Female-Headed Households in Greater Accra Region of Ghana - Kpoor, A. (University of Ghana, 2015)
Over the past 15 years, the Ghana Statistical Service (GSS) in its Ghana Living Standards Surveys (GLSS) has used the consumption expenditure approach and has concluded that female-headed households are better-off than male-headed ones. This conclusion is contrary to the general view that female-headed households are disadvantaged. The consumption expenditure approach has been criticised by scholars for being one-dimensional, as it covers only a limited aspect of male- and female-headed households’ living conditions. In view of this criticism, this study adopts the livelihoods approach - a multidimensional perspective - to capture the multidimensional nature of living conditions in male- and female-headed households in three communities - Adedenkpo, James Town Beach, and Adenkrebi - in the Greater Accra Region of Ghana. Specifically, the study investigates the community, human, social, and financial and economic assets of male- and female-headed households, and how they utilize these assets in their livelihood strategies. The study utilized the concurrent mixed methods approach entailing the use of both quantitative and qualitative data collection techniques. The study communities have different assets endowment and this affects the living conditions of of households. Adenkrebi is more endowed with natural assets than James Town Beach and Adedenkpo which aids households in Adenkrebi to diversify their livelihood activities. On the other hand, Adedenkpo and James Town Beach have more economic assets than Adenkrebi which allow households in these two communities to pursue their livelihood activities. The lack of economic assets such as motorable roads in Adenkrebi makes it difficult for the inhabitants to transport their farm produce to market centres. The findings of the study demonstrate that the livelihoods perspective reveals multiple dimensions of living conditions in male- and female-headed households. Male-headed households have greater human capital assets than female-headed ones; however, the low educational assets of both households confine their members to pursue informal livelihood activities as well as intensification and diversification strategies. The study also indicates that female-headed households have greater social assets than male-headed ones and utilize reciprocal exchange strategies to derive greater resources from CBOs, kin, and neighbours than their male counterparts. Male-headed households also have greater financial and economic assets than female-headed ones. Household income, generated through livelihood activities, is low for both types of households, particularly female-headed ones. However, among other household fiscal assets including savings, treasury bills, shares, and loans, household income is the key financial asset utilized by both household types to satisfy basic household needs. The application of the livelihoods approach in this study demonstrates that male-headed households generally have greater assets endowment and better livelihood outcomes than female-headed ones indicating that they are better-off than their female counterparts. This finding indicates that the consumption expenditure approach masks the deprivations of female-headed households in assets endowment. The study recommends that national surveys that measure the living standards of male- and female-headed households should include assets ownership and livelihoods dimensions in order to capture the multidimensional aspects of living conditions in these two types of households. Furthermore, to assist male- and female-headed households to achieve better livelihood outcomes, there is the need for sustainable natural resource measures to be taken in the study communities, particularly in James Town Beach to ensure that the sea continues to be a viable livelihood source for households. Furthermore, a community asset such as a tarred access road needs to be provided for households in Adenkrebi so that they can effectively pursue their livelihood activities. In addition, current government policies aimed at promoting formal education should be strengthened in the study communities so as to improve and widen the livelihood opportunities of particularly female-headed households in order to increase their asset portfolio. The study contributes to deepening understanding of living conditions of male- and female-headed households from a livelihoods perspective.
Thesis (PHD)- University of Ghana, 2015